Efficacy and immunogenicity of high-dose influenza vaccine in older adults by age, comorbidities, and frailty. Issue 36 (26th August 2015) - DiazGranados, Carlos A.; Dunning, Andrew J.; Robertson, Corwin A.; Talbot, H. Keipp; Landolfi, Victoria; Greenberg, David P.
Abstract: Background: A randomized trial demonstrated that a high-dose inactivated influenza vaccine (IIV-HD) was 24.2% more efficacious than a standard-dose vaccine (IIV-SD) against laboratory-confirmed influenza illness in adults ≥65 years. To evaluate the consistency of IIV-HD benefits, supplemental analyses explored efficacy and immunogenicity by baseline characteristics of special interest. Methods: Double-blind, randomized, active-controlled, multicenter trial. Adults ≥65 years were randomized 1:1 to receive IIV-HD or IIV-SD and followed for 6–8 months postvaccination for the occurrence of influenza. One third of participants were randomly selected to provide sera for measurement of hemagglutination inhibition antibody (HAI) titers. Efficacy (IIV-HD vs. IIV-SD) against laboratory-confirmed, protocol-defined influenza-like illness (PD-ILI) and HAI geometric mean titer (GMT) ratios (IIV-HD/IIV-SD) were evaluated by age, and number of high-risk comorbid and frailty conditions. Results: Efficacy (95% confidence intervals) of IIV-HD relative to IIV-SD against laboratory-confirmed PD-ILI was 19.7% (0.4%; 35.4%) for participants 65–74 years, 32.4% (8.1%; 50.6%) for those ≥75 years, 22.1% (3.9%; 37.0%) for participants with ≥1 high-risk comorbidity, 23.6% (−3.2%; 43.6%) for those with ≥2 high-risk comorbidities, 27.5% (0.4%; 47.4%) for persons with 1 frailty condition, 23.9% (−9.0%; 47.2%) for those with 2 frailty conditions, and 16.0% (−16.3%; 39.4%) for those with ≥3 frailty conditions. There was no evidence of vaccine efficacy heterogeneity within age, comorbidity, and frailty strata ( P -values 0.351, 0.875, and 0.838, respectively). HAI GMT ratios were significantly higher among IIV-HD recipients for all strains and across all subgroups. Conclusions: Estimates of relative efficacy consistently favored IIV-HD over IIV-SD. There was no significant evidence that baseline age, comorbidity, or frailty modified the efficacy of IIV-HD relative to IIV-SD. IIV-HD significantly improved HAI responses for all strains and in all subgroups. IIV-HD is likely to provide benefits beyond IIV-SD for adults ≥65 years, irrespective of age and presence of comorbid or frailty conditions.